Attention and memory protection: Interactions between retrospective attention cueing and interference. Issue 9 (September 2015) - Makovski, Tal; Pertzov, Yoni
Visual working memory (VWM) and attention have a number of features in common, but despite extensive research it is still unclear how the two interact. Can focused attention improve VWM precision? Can it protect VWM from interference? Here we used a partial-report, continuous-response orientation memory task to examine how attention and interference affect different aspects of VWM and how they interact with one another. Both attention and interference were orthogonally manipulated during the retention interval. Attention was manipulated by presenting informative retro-cues, whereas interference was manipulated by introducing a secondary interfering task. Mixture-model analyses revealed that retro-cues, compared to uninformative cues, improved all aspects of performance: Attention increased recall precision and decreased guessing rate and swap-errors (reporting a wrong item in memory). Similarly, performing a secondary task impaired all aspects of the VWM task. In particular, an interaction between retro-cue and secondary task interference was found primarily for swap-errors. Together these results suggest that both the quantity and quality of VWM representations are sensitive to attention cueing and interference modulations, and they highlight the role of attention in protecting the feature–location associations needed to access the correct items in memory.